Deixis in Action: How University Students Construct Meaning in English Classroom Interaction: A Review Study - Susanto, Dias Andris (Global Synthesis in Education Journal, 2026)
This review study explores how deixis functions as a key meaning-making resource in English classroom interaction among university students. Focusing on English learning contexts at Universitas PGRI Semarang and Universitas Islam Negeri (UIN) Walisongo Semarang, Central Java, this article critically synthesizes existing empirical and theoretical studies on deixis within EFL classroom discourse. Drawing on literature published between 2015 and 2025, the review examines how personal, spatial, temporal, discourse, and social deixis are employed by university students to construct, negotiate, and interpret meaning during classroom interaction. The analysis reveals that deictic expressions play a crucial role in shaping interactional coherence, managing turn-taking, establishing participant roles, and contextualizing pedagogical content. Moreover, the findings indicate that students’ use of deixis reflects not only linguistic competence but also pragmatic awareness and sociocultural positioning within academic discourse communities. In Indonesian university settings, deixis is shown to mediate the relationship between language use, instructional context, and student agency, particularly in interactive activities such as discussions, presentations, and collaborative tasks. This review highlights a growing research trend that positions deixis as an essential component of classroom discourse analysis and emphasizes its pedagogical relevance in English language teaching at the tertiary level. The study concludes by identifying gaps in current research, particularly the limited focus on learner-centered deictic practices in diverse institutional contexts, and proposes directions for future discourse-based research on deixis in university EFL classrooms